Medusa Is Actually Laughing: Revisiting US History from a Female Perspective - Šesnić, Jelena (2004)
It is demonstrated on the example of novels written by US ethnic women writers how their strategies of conceptualising history and rewriting dominant genres (historical novel, Bildungsroman) ultimately may bring about a realignment within American literary history, history, and occasion a critique of the normative patterns of gender behaviour.